Behavior of self-compacting concrete incorporating recycle materials at high temperature - Mohamed, Gamal Maged (2015)
The use of Palm Oil Fuel Ash (POFA) only has a limitation of segregation when added up to 15% in concrete, whereby the Pulverized Burnt Clay (PBC) was found to increase the segregation resistance as it acts as viscosity modifying agent. The finer pore pressure distribution along with the poor pore connectivity that Self Compacting Concrete (SCC) exhibits keeps the free and chemically bound water trapped inside the structure leading to a growth in pore pressure. The buildup pressure resulted in the explosive spalling of the concrete particularly at W/B ranging between 0.30 to 0.35 at 30% of blended POFA and PBC. Thus, This research work focus on the effectiveness of both POFA and PBC blended at 0.42 W/B mainly against elevated temperature. The replacement percentages of POFA and PBC are 0/0% (C1 as control mix concrete), 5/5% (C2), 10/10% (C3), 15, 15% (C4) and 20/20% (C5). The residual compressive strength of SCC after exposure to elevated temperatures at 100, 300, 600 and 800 °C was noted. The results revealed that SCC mixes containing higher replacement percentages exhibited excellent workability. For compressive and splitting tensile strength, it was found that C2 and C3 mixes exceeded the strength of control mix at 56 days by 12%, 19 % respectively while C4 and C5 showed lower values than control mix. It was found that behaviors of tested specimen at elevated temperature were improved by the increment of POFA and PBC replacement percentage. C1 showed a continuous decrement in residual compressive strength as temperature increased, while C5 showed an increase in strength by 4% between 100 °C and 300 °C. This could be due to the hydration of anhydrated cement. At 600 °C, C5 gave 10% higher residual compressive strength compared to C1 as well as lower mass loss and no cracks. The mixes with less cement content had shown better behavior at elevated temperatures. Nevertheless, all mixes showed good results when exposed to temperature up to 600°C with no explosion occurred but exploded before temperature reaching 800°C.